PERAN SATBINMAS DALAM MENCEGAH TINDAK KEJAHATAN SEKSUAL KEPADA ANAK DI POLRES CIANJUR - GAGAH ANANDA (Advances in Police Science Research Journal, 2020)
The background of this research problem arises because of an increase in cases of sexual crimes against children from 2016 to 2018. Therefore, a study was conducted to find out the task of the binmas unit, the factors that hinder and how the efforts of members of the community binmas done in preventing cases of child sexual abuse. This research was conducted with a qualitative approach and using research methods in the form of case studies and data collection techniques with interviews, observations and document review. The results of the study found that Satbinmas in the Cianjur area experienced difficulties in carrying out their duties due to lack of personnel, lack of understanding of members and lack of infrastructure. Members of binmas in the Cianjur region complain because they in carrying out their tasks often get double sprin due to the lack of members of binmas personnel. Infrastructure facilities are also incomplete for members of binmas in carrying out tasks such as cameras to carry out documentation, then there are no costs for the maintenance of transportation equipment for Satbinmas members to patrol and visit their assisted residents and sometimes there are still members who do not really understand the material convey to the local community so that the intentions of the members do not convey. Based on the discussion of these findings, the authors conclude several things including (1) Cianjur police chief is encouraged to provide additional personnel, especially to the Bhabinkamtibmas section so that the implementation of tasks in the field is not interrupted, (2) Providing facilities and infrastructure to Bhabinkamtibmas officers Difficulties and obstacles, (3) The need for education / training for members of the Satbinmas in order to deepen their understanding in their duty to maintain the Kamtibmas.